An ultra-fast method of DNA extraction from Neurospora - E. B. Cambareri; J. A. Kinsey (Fungal Genetics Reports, 1993)
We have found that the DNA extraction procedure of Metzenberg and Baitch (Neurospora Newsl. 28:20)/Stevens and Metzenberg (Neurospora Newsl. 29:27) while giving excellent yield and size of DNA, is somewhat cumbersome and also results in the occasional sample that proves to be uncuttable.